(untitled) (Law and world, 2019)
The research includes detailed characterization of inﬂuence peddling. It demonstrates the full description and structure of inﬂuence peddling. Factual and subjective descriptions of inﬂuence peddling, as well as key aspects of qualiﬁcation are also discussed. Main attention is paid to the deﬁnition of the term– inﬂuence. According to the opinions of various authors, this term is quite general, abstract and ambigious, therefore it is necessary the term to be interpreted by the court while hearing individual criminal cases. The article discusses also theoretical and practical differences between inﬂuence peddling and bribe-taking. The research includes detailed description of crime provocation and emphasizes its difference from the abetting crime. Central attention is paid to the issue of provocation from governmental bodies during secret investigative activities. At the end of the research the author provides several recommendations about the deﬁnition of the term– inﬂuence and on the issue of making standards of crime provocation stricter and closer to the European standards.